Struggling beyond the paradigm of Neoliberalism. (June 2020) - Welsh, John
Whilst the Neoliberal alludes to an array of very real material practices and axioms of contemporary capitalism, the concept of Neoliberalism itself has arguably become moribund. Worse, perhaps it has become an asphyxiating and enervating monolith, a 'ptolemization' from which our critical thinking cannot escape. The key strategy of the article is to explore the Neoliberalism concept as a 'mode of telling', and how the constitutive moments of that concept have been discursively constructed into a hegemonic discursive formation. Whilst the resultant paradigm of Neoliberalism has ironically been constituted out of the identity-thinking and the synthetic historicizing of its very critics, the article searches for alternative avenues of reconstitutive deconstruction, so as to offer both critical optimism and a more effective means of struggle against the material practices of contemporary capitalism. To this end, I shall indicate how overdetermination in conceptualization provides the opportunity to break down identity-thinking and how articulation can translate the material elements of contemporary capitalism into fresh moments of a counter-hegemonic discourse.